2010
DOI: 10.1007/s12098-010-0214-y
|View full text |Cite
|
Sign up to set email alerts
|

Airway Pressure Release Ventilation: An Alternative Ventilation Mode for Pediatric Acute Hypoxemic Respiratory Failure

Abstract: Airway pressure release ventilation (APRV) is a relatively new mode of mechanical ventilation. The use of this model of ventilation in pediatrics has been limited. The authors describe their experience with this mode of ventilation in a series of pediatric hypoxemic respiratory failure patients. Three patients with acute hypoxemic respiratory failure (AHRF) were treated with APRV, when oxygenation did not improve with pressure control ventilation (PCV). The mean age of the patients was 5.8 ± 1.3 months. Fracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 10 publications
0
8
0
3
Order By: Relevance
“…Demirkol et al, 3 refieren la optimización de la vía aérea, lo cual mejora el reclutamiento mediante la estabilización de pulmón abierto.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Demirkol et al, 3 refieren la optimización de la vía aérea, lo cual mejora el reclutamiento mediante la estabilización de pulmón abierto.…”
Section: Discussionunclassified
“…Su modalidad consiste en un ajuste de alta presión (p alto) hacia un límite de baja presión predeterminado (P bajo), dando lugar a un mecanismo de ventilación que utiliza presión positiva controlada en la vía aérea, con el fin de maximizar el reclutamiento alveolar mediante las comunicaciones bronquiales colaterales, y permite la respiración espontánea durante ambas fases del ciclo respiratorio. 3 Permite mayor reclutamiento alveolar, debido a una larga fase inspiratoria, lo que hace innecesario aumentar el volumen corriente o sumar presión positiva a la vía aérea. Al permitir respiraciones espontáneas, mejora también el llenado cardiaco.…”
Section: Caso Clínicounclassified
“…APRV is a modification of CPAP (7). The addition of the pressure-relief valve in exhale branch allowed pressure control, time trigger, pressure limit and time switch, and spontaneous breath in the respiratory cycle (7). High pressure maintained alveolar recruitment while low pressure facilitated expelling CO 2 and maintained open alveoli of diffusion constant.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that PEEP guided by PMC was reasonable and significantly higher than that guided by LIP, leading to significant unfavorable impact on ventilation and blood flow as well as a higher risk of ventilator-induced lung injury (VILI) (4–6). Airway pressure release ventilation (APRV) involved the modification of continuous positive airway pressure (CPAP), and had been proven to decrease mean arterial pressure (MAP), as well as improve hemodynamics and alveolar collapse and prevent barotrauma (7–9). …”
Section: Introductionmentioning
confidence: 99%
“…Even though APRV is being used more widely in adult critical care units internationally to facilitate open lung ventilation, information surrounding its safety and effectiveness in pediatric patients is limited . We conducted a retrospective chart review of those patients with acute respiratory distress syndrome (ARDS) who received APRV in a medical‐surgical pediatric intensive care unit (PICU) to better describe the use of this ventilation modality in critically ill pediatric patients.…”
Section: Introductionmentioning
confidence: 99%